Impact Of Pressurized Extraction And Electrohydrodynamic Encapsulation Methods On Antioxidative Properties Of Momordica Charantia Fruit Extract - Torkamani, Amirehsan (2018)
The objectives of this study were first to model pressure assisted extraction of polyphenolic antioxidants from bitter gourd (BG) as a model fruit-like vegetable and secondly to characterize electrohydrodynamic nanoencapsulation methods within natural polymeric matrices. Response surface methodology (RSM) was used to investigate and optimize the impact of extraction time, temperature and induced calorimetric power on total phenolic content (TPC), total flavonoid content (TFC), Ferric reducing/antioxidant power assay (FRAP) and Radical scavenging activity (RSA) of BG ultrasonic assisted extract (UAE).